2012
DOI: 10.1155/2012/743947
|View full text |Cite
|
Sign up to set email alerts
|

A New Ruthenium Sensitizer Containing Benzo[1,9]quinolizino(acridin-2-yl)vinyl-2,2′-bipyridine Ligand for Effective Nanocrystalline Dye-Sensitized Solar Cells

Abstract: Novel ruthenium bipyridyl sensitizer incorporating conjugated benzo[1,9]quinolizino-(acridin-2-yl)vinyl-2,2′-bipyridine ligand [JJ-12] has been synthesized and demonstrated as efficient sensitizer in dye-sensitized solar cells. A mesoporous titania film stained withJJ-12exhibits a remarkable incident monochromatic photon-to-current conversion efficiency of 82%. Under standard AM 1.5 sunlight, the solar cell using a liquid-based electrolyte consisting of 0.6 M 1,2-dimethyl-3-propylimidazolium iodide (DMPII), 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Kim et al 108 reported a novel ruthenium bpy sensitizer, 63 (JJ-12), incorporating the highly conjugated benzo [1,9]quinolizino-(acridin-2-yl)vinyl-2,2-bpy ligand and its excellent photovoltaic performances in DSSCs. Owing to increased π-conjugation in the ancillary ligand and the donor capability of benzo [1,9]quinolizinoacridine, the low-energy MLCT band of JJ-12 was 10 nm red-shifted relative to that of N3.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…Kim et al 108 reported a novel ruthenium bpy sensitizer, 63 (JJ-12), incorporating the highly conjugated benzo [1,9]quinolizino-(acridin-2-yl)vinyl-2,2-bpy ligand and its excellent photovoltaic performances in DSSCs. Owing to increased π-conjugation in the ancillary ligand and the donor capability of benzo [1,9]quinolizinoacridine, the low-energy MLCT band of JJ-12 was 10 nm red-shifted relative to that of N3.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…Of a more recent vintage are polycyclic, planarized TAs with enhanced π-conjugation. Examples of such planar TAs (see Figure ) are dimethylmethylene-bridged MeTA ( MeTA = 4,4,8,8,12,12-hexamethyl-4 H ,8 H ,12 H -benzo­[1,9]­quinolizino-[3,4,5,6,7- defg ]­acridine), where the methylene straps prevent the twisting of the phenyl rings around the C–N bonds, and the oxygen-bridged analogue TOTA ( TOTA = 2,2′:6′,2″:6″,6-trioxotriphenylamine), which is bowl shaped in the neutral state but completely planar as the radical cation. , 2,2′:6′,2″-Dioxotriphenylamine ( DOTA ) with one fewer ether strap is in contrast skewed with an interplanar angle of 43.0° between the unbridged phenyl rings, which is reduced to 38.3° after oxidation to its radical cation. , …”
Section: Introductionmentioning
confidence: 99%